Role Big Big Bhabinkamtibmas in Prevention Action Motorcycle Theft Crime at Dau Police Section, Malang Police Regency - Djabar, Fauzan Setiawan; Novena Monalisa, Theresia; Yusuf Ramadhan, Sardika (Tanggon Kosala, 2025)
Motorcycle theft is a crime that causes concern for the community. The rampant incidents of motorcycle theft that occur in the jurisdiction of the Dau Police, Malang Police, are a disturbance to public order that is very disturbing to the community. The police are the guardians of the community who are obliged to maintain public order through the Binmas function by carrying out bimluh activities as a form of real action to increase public awareness regarding motorcycle theft. This study aims to describe the phenomenon of motorcycle theft, analyze the role of bimluh activities by Bhabinkamtibmas, analyze the factors that influence the role of bimluh and reviewing relevant theories and concepts in preventing motorcycle theft. This study concludes that the role of the bhabinkamtibmas bimluh in preventing motorcycle theft has not been appropriately implemented. 2 factors influence the role of the bhabinkamtibmas bimluh, namely internal factors, including the lack of quality and quantity of personnel and external factors, such as the lack of public awareness of preventing motorcycle theft. This study suggests that the methods and targets of the Bhabinkamtibmas bimluh must be more appropriate in preventing motorcycle theft and that the Bhabinkamtibmas work together with related parties in preventing motorcycle theft.